Perancangan Sistem Arsitektur Untuk Sistem Informasi Penerimaan Mahasiswa Baru - Jayanti, Sherly (STMIK Palangkaraya, 2016)
New admissions is a regular activity performed each year. Each year, an increase of students who will enroll. This is evident from the number of prospective students are always increasing and enthusiastic to register on STMIK Palangka Raya. The existing system is still not fully integrated and lack of network infrastructure for data exchange so as not supporting the effectiveness of the work on the new admissions. It is necessary for the design of the system architecture of the network infrastructure for integrating existing information systems so as to achieve the vision and mission of the College. To illustrate the design is based on a theoretical basis, using Edraw Max 7. This study uses a framework approach Shelly Cashman namely initialization and total cost of ownership (TCO), scalability, electoral process and security issues. The end result of this research is the blueprint proposed system architecture on Information Systems Admissions STMIK Palangka Raya.